Post‐hoc analysis of the tofogliflozin post‐marketing surveillance study (J‐STEP/LT): Tofogliflozin improves liver function in type 2 diabetes patients regardless of BMI - Hiroyuki Uchinuma; Mitsunori Matsushita; Masaya Tanahashi; Hideki Suganami; Kazunori Utsunomiya; Kohei Kaku; Kyoichiro Tsuchiya (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction Patients with type 2 diabetes are at high risk of developing steatotic liver disease (SLD). Weight loss has proven effective in treating metabolic dysfunction‐associated steatotic liver disease (MASLD) in obese patients with type 2 diabetes, with sodium‐glucose cotransporter 2 (SGLT2) inhibitors showing promising results. However, lean MASLD is more prevalent in Japan, necessitating alternative approaches to body weight reduction. Materials and Methods We used the J‐STEP/LT dataset including up to 3‐year treatment data to analyze the effects of the SGLT2 inhibitor tofogliflozin on liver function and treatment safety and conducted a subgroup analysis based on body mass index (BMI; kg/m2, <20, 20–<23, 23–<25, 25–<30, and ≥30). Results This study included 4,208 participants. Tofogliflozin significantly reduced alanine aminotransferase (ALT) levels in participants with baseline ALT levels >30 U/L across all BMI groups, with median changes of −12, −16, −13, −15, and −15 U/L, respectively (P = 0.9291 for trends). However, median changes in body weight with tofogliflozin were −2.00, −2.75, −2.00, −3.00, and −3.80 kg, respectively (P < 0.0001 for trends), with no significant weight loss observed in the BMI <20 group. ALT levels were also significantly decreased in participants who did not lose weight. Safety assessments according to BMI and age categories revealed no clear differences in the frequency of adverse events. Conclusions Tofogliflozin reduced ALT levels without substantial body weight reduction among lean participants. These findings suggest that SGLT2 inhibitors may be a viable treatment option for non‐obese patients with type 2 diabetes and SLD.